Pengaruh Metode Latihan Drill Terhadap Kemampuan Servis Bawah pada Permainan Bola Voli - Aji Suryo Putro, Waskito; Derlean, Iriani; Nursalim; Anwar, Saiful (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2024)
Volleyball learning activities at SD Muhammadiyah 2 Sorong City are considered successful, especially in teaching basic techniques such as top serve. However, many students struggle in the often ineffective underserve. This study uses a quantitative approach to test the influence of the drill practice method on the ability to serve under grade VI students. The results showed that the drill method was effective in significantly improving the ability to serve the underside, as evidenced by the difference in higher and consistent average values in the experimental group compared to the control group. The hypothesis test confirmed this difference with a significance value of 0.000. These findings confirm the importance of drill training to improve students' sports skills optimally. Key words: Drill Drill, Lower Service Ability